Clinical course and physiotherapy intervention in 9 patients with COVID-19. (December 2020) - Lee, Audrey Jia Yi; Chung, Chloe Lau Ha; Young, Barnaby Edward; Ling, Li Min; Ho, Benjamin Choon Heng; Puah, Ser Hon; Iqbal, Saboor Rahman; Tan, Geak Poh
Abstract: Since the outbreak of the 2019 novel coronavirus (COVID-19), the role of physiotherapy for patients with COVID-19 infection has been highlighted by various international guidelines. Despite that, clinical information regarding the rehabilitation of patients with COVID-19 infection remains limited. In this case series, we provide a novel insight into the physiotherapy management in patients infected with COVID-19 in Singapore. The main findings are: (1) Respiratory physiotherapy interventions were not indicated in the majority of the patients with COVID-19 in this case series; (2) During rehabilitation, exertional or position-related desaturation is a common feature observed in critically ill patients with COVID-19 infection locally. This clinical phenomenon of exertional or positional-related desaturation has significantly slowed down the progression of rehabilitation in our patients. As such, it can potentially result in a significant burden on healthcare resources to provide rehabilitation to these patients. Based on these findings, we have highlighted several recommendations for the provision of rehabilitation in patients who are critically ill with COVID-19.